The Relationship between Cyberbullying in High School Students with Sociodemography, Narcissistic Characteristics, Self-Efficacy and Attitudes - Sinem Yıldız İnanıcı; Selda Küçük Akdere; Emine Çelik; Sümeyye Akçay Arısoy Ekşilioğlu; Mehmet Akif İnanıcı (Adli Tıp Bülteni, 2022)

(untitled)
Objective:With the rapid development of technological devices and the increase in access opportunities, cyberbullying is becoming more common among young people. This study’s aim is to describe the demographic, psychological and environmental factors associated with cyberbullying experiences in high school students.Methods:This study was conducted with 431 high school students with a mean age of 16.01, 52.2% of whom were girls. The form used includes demographics, risk behaviors, school and family perceptions, risky behaviors on the internet, and Cyberbullying, Children’s Self-Efficacy and, Childhood Narcissism Scales.Results:The girls’ rate is higher than the boys’ in the non-participant and victim groups. Harmful substance use is the highest in the bullyvictim group. In addition, the rate of owning personal computers is higher than other groups in bully-victims and, they pretend to be a different person on the internet. Those who use the Internet to find new friends, pretend to be a different person on the Internet, and share their private information with strangers have higher narcissism scores than those who do not. Grade and having close friends who show antisocial type behaviors predicts victimization. Having personal computer, grade, truancy and finding easy to bully other people predicted being in a bully/victim group. Narcissism did not mediate the relationship between self-efficacy sub-dimensions with cyberbullying groups.Conclusion:Cyberbullying is associated with many individual and social factors. To investigate the mediating effects of narcissistic characteristics, it may be suggested to examine the types of narcissism and the factors affecting attitudes towards bullying.